Storytelling Practices in Home and Educational Contexts Perspectives from Conversation Analysis - Filipi, Anna.; Ta, Binh Thanh; Theobald, Maryanne (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book brings together researchers from across the globe to share their work on the micro-analyses of storytelling. By doing so, the book helps to deepen the understanding of, and track storytelling practices cross-culturally and longitudinally in the home, at school, and in higher education. Through the unique focus on education and learning, this book provides a lens with which to identify how children's and adolescents' language development and sense of self in storytelling are supported in various contexts: the home, classroom, playground or in the higher education context. It explores the work, identity and practices of friends, teachers and lecturers in teaching, learning, reflection and supervision. Importantly, in identifying these practices, the book presents opportunities to assist parents and teachers, to inform pedagogy in teacher education, and to support effective doctoral supervision. The focus on storytelling in homes, education, and for learning, and the practical applications of the findings, contribute to the ongoing research in both education and conversation analysis. Chapter 10 is available open access under a Creative Commons Attribution 4.0 International License via link.springer.com.
Introduction -- 1 The centrality of storytelling to human interaction -- Section 1 Storytelling in the family -- 2 The shape and functions of pretend play in interactions with a parent: First stories -- 3 The stories we tell: Stories within family settings -- 4 (TBC - Storytelling practices in parent child interaction) -- 5 Recipiency around the Dinner Table: Aligning, Disaligning and Misaligning with a storytelling -- Part 2 Storytelling in school -- 6 Enduring storytelling dispositions in early childhood education -- 7 Short stories in culturally and linguistically diverse classrooms -- 8 The collaborative emergence of storytelling in an after-school foreign language primary classroom -- 9 Tellings in tests: Some constraints on storytelling sequences in L2 oral proficiency tests -- 10 "Did the teacher ...": The storytelling practices of two English Language Learners -- 11 Reconstructing refugee students' experience of classroom practices from their tellings -- Part 3 Storytelling in Higher Education -- 12 Teacher storytelling in an English as a Second Language 'meaning -and-fluency' class -- 13 "I remember when I was in Valencia": Student-teacher story-telling and co-construction of identities -- 14 Giving advice through hypothetical storytelling: A Conversation Analytic study of supervisory interaction between doctoral students and supervisors -- Conclusion -- 15 Considerations for parenting and educating.
Keywords: Educational sociology; Education; Children; Education, Higher; Teachers-Training of; Sociology of Education; Childhood Education; Higher Education; Teaching and Teacher Education